An optimisation research on two-dimensional age-replacement interval of two-dimensional products. (2018) - Wu, Yutao; Song, Wenyuan; Bai, Yongsheng; Han, Yucheng; Cao, Wenbin
For the failures of two-dimensional products affected by the calendar time and usage time, traditional one-dimensional preventive maintenance cannot satisfy the actual maintenance demand of two-dimensional products. Therefore, this paper proposes two-dimensional preventive maintenance strategy for two-dimensional products and makes decision for two-dimensional products through calendar time and usage time. Firstly, we establish failure rate function expression of two-dimensional products and analyse the process of two-dimensional preventive maintenance in detail, after proposing a cost model and availability model from the view of economy and mission in finite span. According to the cost and availability model, through examples, we derive the optimal two-dimensional age-replacement interval by numerical algorithm and particle swarm algorithm, and verify the model's applicability and validity through contrast and analysis. Lastly, we give a brief discussion of future research area about two-dimensional maintenance.